Distribution and breeding numbers of a recently split species, the West African Crested Tern Thalasseus albididorsalis. (28th October 2022) - Veen, Jan; Amarejeyat, Ahmed; el Agbani, Mohamed Aziz; Camara, Mohamed; Dallmeijer, Hanneke; Diawara, Yelli; Diop, Moussa Sega; Diouf, Abdou; Folmer, Eelke; Gomis, Nicolas; Mansali, Valentin; Monteira, Hamilton; et al.
Abstract : This study investigated the distribution, numbers and conservation threats of the West African Crested Tern, which was recently elevated to full species after it was split from the Royal Tern with an American and African subspecies. In the period 1998–2019, a total of 13 West African coastal islands were identified as breeding localities, stretching from Mauritania to Guinea. All the islands are isolated, usually sandy and subject to erosion. There was great yearly variation in the numbers of breeding pairs within and between sites. A complete census of all breeding locations in 2015 and 2019 resulted in estimates of 79 000 and 77 000 pairs, respectively. The threats identified are predation, human disturbance, nest flooding and loss of breeding habitat as a result of coastal erosion. Predation of eggs and chicks by Sacred Ibises and especially Great White Pelicans may heavily impact on the species' breeding output. Human disturbance is slight because most of the breeding islands are within protected areas. Flooding of nests has increasingly been observed in recent years, occurring at nine of 11 islands occupied by the terns in 2015. Most islands are subject to erosion, which has resulted in substantial loss of suitable breeding habitat over the 22-year study period. Two important islands have become completely unsuitable. We conclude that West African Crested Terns have an uncertain future. Food shortage resulting from industrial fishing is suspected, and the effects of climate change might negatively impact on habitat suitability and food availability. Monitoring of the total population at three-year intervals is recommended.